Perancangan Pertanian Unggul dengan Sistem TI-FARM Menggunakan Metode Agile - Putri Nadia Ayu Rahmawati; Nur Jannah; Ahmad Chusyairi (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2019)
Agriculture in Singojuruh Subdistrict, Banyuwangi Regency, East Java Province has 57 Farmers Groups in 11 villages (Alas Malang, Benelan Kidul, Gambor, Singojuruh, Singolatren, Lemahbang Kulon, Gumirih, Padang, Cantuk, Kemiri, and Sumber Baru) in which need information on organic and inorganic agriculture for agricultural processing, including: piracy, irrigation, fertilization, planting and pest control. In an effort to facilitate farmers in knowing information on organic and inorganic agriculture, a web-based ITFARM system is needed. The approach used in this research is a qualitative approach with observation, interview and literature study as well as using agile methods for timebox planning, Daily Stand-Up Meeting (Elicitation Requirements, Detail System Design, Coding Development & Testing), Demonstration and Retrospective Meeting. IT-FARM system users, namely: farmers, Agricultural Counseling Centers (BPP) and administrators. The conclusion obtained in this study is a Web-based IT-FARM system built using the agile method where the web can inform how to plant, pirate, irrigate, fertilize, and control pests both organic and inorganic agriculture. BPP Singojuruh Subdistrict, Banyuwangi Regency, East Java Province can use the TI-FARM system for materials that can be delivered to farmer groups to go to Superior Agriculture. Admin can manage data about organic and inorganic agriculture. Information about agriculture can be seen by the BPP and the Farmers' Group.